2012
DOI: 10.1557/opl.2012.392
|View full text |Cite
|
Sign up to set email alerts
|

The Nanoporous Metallisation of Insulating Substrates through Photocatalytically Initiated Electroless Deposition (PIED)

Abstract: We report the novel use of semiconductor photocatalysis for the deposition of metal onto insulating surfaces and the in-process formation of nano-structured porosity within this metal. In the process of Photocatalytically Initiated Electroless Deposition (PIED) we have developed a controllable, spatially selective and versatile metallisation technique with several advantages over traditional, non-photocatalytic techniques such as enhanced controllability and purity of the deposit as well as reduced operational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…As previously described in our studies of the metallisation of glass substrates with nanoporous metal films (4, 7), hexagonally close packed arrays of 1 µm microspheres provide the template material around which PIED generated nanoporous metal film may be formed. We have found that such microsphere array templates may also be deposited onto the PVDF membrane substrates in the same manner as on glass, although the spheres exhibit less regular packing on membranes than on similarly prepared glass substrates (4,11). This may be attributable to two factors; firstly, the rough surface morphology of the PVDF membrane, Figure 3, disrupting the self-assembly process of the microspheres, leading to an increased number of dislocations within the array; and secondly, the potentially reduced efficiency of the non-annealed photocatalyst resulting in the super-hydrophilicity of the irradiated TiO 2 surface (9, 12) being less readily generated and the microsphere suspension spreading less freely over the substrate surface.…”
Section: Microsphere Array Formationmentioning
confidence: 94%
See 2 more Smart Citations
“…As previously described in our studies of the metallisation of glass substrates with nanoporous metal films (4, 7), hexagonally close packed arrays of 1 µm microspheres provide the template material around which PIED generated nanoporous metal film may be formed. We have found that such microsphere array templates may also be deposited onto the PVDF membrane substrates in the same manner as on glass, although the spheres exhibit less regular packing on membranes than on similarly prepared glass substrates (4,11). This may be attributable to two factors; firstly, the rough surface morphology of the PVDF membrane, Figure 3, disrupting the self-assembly process of the microspheres, leading to an increased number of dislocations within the array; and secondly, the potentially reduced efficiency of the non-annealed photocatalyst resulting in the super-hydrophilicity of the irradiated TiO 2 surface (9, 12) being less readily generated and the microsphere suspension spreading less freely over the substrate surface.…”
Section: Microsphere Array Formationmentioning
confidence: 94%
“…These activities are important in a wide range of industries including pharmaceuticals, mining, foodstuffs, wastewater processing, power generation and nuclear. Using our recently reported insulator metallisation process of Photocatalytically Initiated Electroless Deposition (PIED) (1)(2)(3)(4), we aim to develop novel, highly ion selective membrane-based separation technologies through a combination of supported ligand membranes and supplemental electrochemical control by overlying nano-engineered metal layers. Layers of porous metal with controllable pore size, distribution and metal thickness deposited on ion selective membranes (ISMs) may act as in-situ electrodes offering electrochemical control over the environment at the ISM-solution interface.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation